The comparative effectiveness of progressive relaxation training on pain characteristics, attack frequency, activity self-efficacy, and pain-related disability in women with episodic tension-type headache and migraine - Aysenur Karakus; Esra Uzelpasaci; Gokcen Akyurek (PLoS ONE, 2025)
Background and purpose Episodic tension headache (TTH) and migraine, both categorized as primary headache types, account for 60–90% of headache complaints and are three times more common among young women. This study aimed to explore the comparative effectiveness of progressive relaxation training (PRT) on pain characteristics, attack frequency, activity self-efficacy, and pain-related disability in women with episodic TTH and migraine. Materials and methods This study was registered at ClinicalTrials.gov (NCT06050382). This prospective study included women with episodic TTH (n=20) and migraine (n=20). The pain intensity, impact of headaches on life, activity self-efficacy, pain catastrophizing, and pain-related disability levels of both groups were measured using the Visual Analog Scale (VAS), Headache Impact Test (HIT-6), Occupational Self-Assessment Scale (OSAS), Pain Catastrophizing Scale (PCS), and World Health Organization Disability Assessment Schedule 2 (WHODAS-II) pre- and post-intervention, respectively. Both TTH and migraine groups received PRT twice a week for six weeks, Results Within-group comparisons showed significant decreases in attack frequency, VAS, HIT-6, PCS, and WHODAS-II scores in both groups post-intervention (p<0.001). Also, both groups showed an increase in OSAS proficiency scores (p<0.001). The between-group comparison showed that the attack frequency, VAS, HIT-6, PCS, and WHODAS-II scores were lower in the migraine group than the TTH group. However, all sub-scores of the OSAS were higher in the migraine group (p<0.001). Conclusions PRT showed positive effects on pain intensity, attack frequency, activity self-efficacy, and pain-related disability in both groups, more so in the TTH group.